2017
DOI: 10.1371/journal.pone.0176196
|View full text |Cite
|
Sign up to set email alerts
|

ClC-3 chloride channel mediates the role of parathyroid hormone [1-34] on osteogenic differentiation of osteoblasts

Abstract: IntroductionDifferent concentrations of parathyroid hormone [1–34] (PTH [1–34]) can have totally opposite effects on osteoblasts. Intermittent stimulation with PTH can significantly increase bone mineral density in vitro, mainly through the protein kinase A (PKA) signaling pathway, which phosphorylates runt-related transcription factor 2 (Runx2). The ClC-3 chloride channel, an important anion channel, can also promote osteogenesis via the Runx2 pathway based on recent studies. The purpose of our study, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…After mineralization in bone matrix, deposition of calcium around bone tissue can be detected by calcium staining experiments, including Alizarin Red S 7 . The mineralization of bone matrix is mainly promoted by induction of collagen type I alpha 1 chain (COL1A1), 8 osteocalcin (OC), 9 osteopontin (OPN), 10 bone sialoprotein (BSP), 11 transforming growth factors‐β (TGF‐β), 12 and bone morphogenic proteins (BMPs) 13 . Moreover, Runt‐related transcription factor 2 (RUNX2), 14 osterix (OSX), 15 distal‐less homeobox 5 (DLX5), 16 and β‐catenin 17 are known to play a pivotal role in osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…After mineralization in bone matrix, deposition of calcium around bone tissue can be detected by calcium staining experiments, including Alizarin Red S 7 . The mineralization of bone matrix is mainly promoted by induction of collagen type I alpha 1 chain (COL1A1), 8 osteocalcin (OC), 9 osteopontin (OPN), 10 bone sialoprotein (BSP), 11 transforming growth factors‐β (TGF‐β), 12 and bone morphogenic proteins (BMPs) 13 . Moreover, Runt‐related transcription factor 2 (RUNX2), 14 osterix (OSX), 15 distal‐less homeobox 5 (DLX5), 16 and β‐catenin 17 are known to play a pivotal role in osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, when we knocked down the expression of ClC-3 and Smad2/3/4 together, we found that ALP activity and Runx2 and Osx levels were also decreased, but the extent was less pronounced than the effects of their inhibition alone, except for the Collagen I protein. This is probably related to the fact that Collagen I is a major component of the matrix and regulates the adhesion and bone-guiding function of mature osteoblasts after differentiation,; nevertheless, the ClC-3 chloride channel is mainly involved in regulating the osteoblast differentiation process [ 7 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that ClC-3 chloride channels are closely related to bone metabolism. Clcn3-knockout mice displayed complex genetic phenotypes, including stunting, kyphosis, and abnormalities in calcium and phosphorous metabolism [ 6 , 7 ]. Furthermore, we discovered that ClC-3 chloride channels are expressed by osteogenic lineage cells and regulate osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the expression of the ClC-3 chloride channel in osteoblasts is conducive to the stimulation of PTH by osteoblasts, thus mediating the differentiation of osteoblasts. 76 The ClC-3 chloride channel regulates the bone formation function of osteoblasts by regulating the estrogen a receptor. 77 , 78 The increased expression levels of ClC-3 chlorine channel proteins can upregulate the expression of the downstream Runx2 gene, thus promoting osteogenic differentiation.…”
Section: The Epidemiology Of Bone Aging and Senile Osteoporosismentioning
confidence: 99%